Optically Transparent Wood from a Nanoporous Cellulosic Template: Combining Functional and Structural Performance - Li, Yuanyuan; Fu, Qiliang; Yu, Shun; Yan, Min; Berglund, Lars (Biomacromolecules, 2016)
Optically transparent wood (TW) with transmittance as high as 85% and haze of 71% was obtained using a delignified nanoporous wood template. The template was prepared by removing the light-absorbing lignin component, creating nanoporosity in the wood cell wall. Transparent wood was prepared by successful impregnation of lumen and the nanoscale cellulose fiber network in the cell wall with refractive-index-matched prepolymerized methyl methacrylate (MMA). During the process, the hierarchical wood structure was preserved. Optical properties of TW are tunable by changing the cellulose volume fraction. The synergy between wood and PMMA was observed for mechanical properties. Lightweight and strong transparent wood is a potential candidate for lightweight low-cost, light-transmitting buildings and transparent solar cell windows.